The New Philanthropy, Poverty Reduction and Rural Development: A Case Study of Alliance for a Green Revolution in Africa (AGRA) in Ghana - I ASURU, SUMAILA (Universitas Muhammadiyah Yogyakarta, 2015)
This study seeks to explore the significant contributions of the new philanthropy towards improving the conditions of smallholder farmers in Sub-Saharan African, smallholder farmersâ€™ understanding of philanthropy and to investigate the relationship that exists between philanthropy and smallholder farmers. The research is designed to uncover the needs and drivers of both philanthropy and smallholder farmers in relation to their interaction and the fulfilment of the philanthropic contract they have entered into. The main objective of the thesis is to consider the potential of philanthropy to rural transformation for poverty reduction. It focus is the involvement of the Bill and Melinda Gates Foundation in rural development and poverty reduction in Ghana. Since 2006 the Bill and Melinda Gates Foundation (Gates Foundation) has dedicated 1.7 billion to assisting smallholder farmers. The bulk of this investment has been delivered through programmesÂ associated with the Alliance for a Green Revolution in Africa (AGRA), which is also supported by the Rockefeller Foundation(Thompson, 2012). This study observed an inherent discrepancies and organisational miscalculations that have adverse influence on the effective collaboration and implementation of philanthropic support to the selected farmers. Untimely release of farming inputs as well as exceedingly unfavourable conditions for the attractions of loans makes it difficult for smooth farming. This exercise also established that both men and women intercrop their farms to ensure household food securityand income. Household decisions on which medium of farming to pursue and on use of the income from farming are generally taken by men. Due to these, this research emphasise that philanthropic offering in Ghana should be looked at dispassionately bearing in mind the socio-culturally diverse nature of thecountry itself as well as key environmental factors that hugely contributeto poverty.KEYWORD:Philanthropy, Poverty Reduction, Green Revolution, RuralDevelopment, Ghana